I want to celebrate as hymns acculturation of i will sing of my redeemer (an analysis on a Sangihe Masamper song) - Glenie Latuni (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This research aims to analyze the acculturation process through the hymn I will sing of my Redeemer, which became Hymn MasamperI Want To Celebrate. I will use a qualitative approach to explore the perspective of ethnomusicology and hymnology through observation, interviews, and literature review. Observations have been made for a long time because the researcher is also the artist of Masamper Art. But the focus of observation from 2008 until now has been Observations were made on various Masamper performances in the Sangihe community in the Sangihe Islands and the Sangihe diaspora community on the mainland of North Sulawesi in the city of Manado. The results of the analysis found that the existence of the song